Veliparib and nivolumab in combination with platinum doublet chemotherapy in patients with metastatic or advanced non-small cell lung cancer: A phase 1 dose escalation study. (November 2021) - Clarke, Jeffrey M.; Patel, Jyoti D.; Robert, Francisco; Kio, Ebenezer A.; Thara, Eddie; Ross Camidge, D.; Dunbar, Martin; Nuthalapati, Silpa; Dinh, Minh H.; Bach, Bruce A.
Highlights: Veliparib, a PARP inhibitor, enhances cytotoxicity induced by chemotherapy (CT). Nivolumab, a PD-1 inhibitor, plus CT demonstrated efficacy for NSCLC treatment. This is a phase 1 trial of veliparib + nivolumab + CT in unresectable stage III NSCLC. This quadruple therapy was tolerated, and no drug-drug interaction was observed. This combination suggests promising antitumor activity. Abstract: Objectives: Both combinations of the PARP inhibitor veliparib plus platinum doublet chemotherapy (CT), and the programmed death receptor-1 (PD-1) inhibitor nivolumab plus CT have demonstrated encouraging efficacy for treatment of non-small cell lung cancer (NSCLC). This phase 1 dose-escalation study (NCT02944396) evaluated the quadruple combination of veliparib with nivolumab and doublet CT in patients with unresectable advanced/metastatic NSCLC. Materials and methods: Patients were enrolled into five dosing cohorts: patients received veliparib 120 mg twice daily (BID) combined with nivolumab 360 mg, carboplatin AUC 6 mg/mL∙min, and paclitaxel 200 mg/m 2 (C/PAC) or veliparib 80/120/200/240 mg BID in combination with nivolumab 360 mg, carboplatin AUC 6 mg/mL∙min, and pemetrexed 500 mg/m 2 (C/PEM). Primary objective was to identify the recommended phase 2 dose (RP2D) of veliparib + nivolumab + CT. Safety, tolerability, and efficacy of this combination were also assessed. Results: Twenty-five patients were enrolled: 6 patients received veliparib 120 mg BID + nivolumab + C/PAC and 19 received veliparib (80–240 mg BID) + nivolumab + C/PEM. No dose-limiting toxicities were reported, and the RP2Ds were veliparib 120 mg BID + nivolumab + C/PAC, and veliparib 240 mg BID + nivolumab + C/PEM. The most common any-grade adverse events (AEs) were fatigue (56%), nausea (52%), and anemia (48%). Grade 3/4 AEs included anemia (32%) and neutropenia (24%), and the most frequent serious AE was malignant neoplasm progression (12%). Veliparib exhibited approximately dose proportional kinetics in the dose range 80–240 mg BID combined with nivolumab and C/PEM, with no effects on pemetrexed pharmacokinetics. Overall, the confirmed objective response rate was 40%, and best overall response was 64%. Conclusion: Veliparib combined with nivolumab and platinum doublet CT was tolerated in patients with advanced/metastatic NSCLC, and no evidence of drug–drug interaction was observed. Although preliminary, this quadruple therapy may have promising antitumor activity.